The Extend of Applying the Extensible Business Reporting Language at Jordanian Industrial Companies - Tawfik, Omar Ikbal; Hayek, Ahmad Faisal; Al-Smady, Ahnaf Ali (International Review of Management and Marketing, 2017)
The purpose of this study is to the Extend of Applying the Extensible Business Reporting Language (XBRL) at Jordanian Industrial Companies the aim is to identify the role of this language in developing electronic publishing information in Jordan, The study had been formed five hypotheses to test these variables and the relation among them, for this purpose the study had a questionnaire distributed to a sample of (90) person representing the community. The most important results show: That the Laws and regulations, organizational factors, Individuals working, technical factors applied in the Jordanian industrial companies support the application of the language of the expanded business reports Keywords: Extensible Business Reporting Language (XBRL), Environmental Factors, Jordanian Industrial Companies. JEL Classifications: L15, Q56